El Niño Shuá: del estereotipo a la reivindicación de la vida y obra de Miguel Ángel Jusayú - Nelly García Gavidia; Carlos Adán Valbuena Chirinos; Carmen Laura Paz Reverol (Les Cahiers ALHIM)
We take a journey through the life and work of the master Miguel Ángel Jusayú (1933-2008), with the purpose of analyzing, based on his autobiography and the film El Niño Shuá by Patricia Ortega, the most difficult moments after the loss of the vision and the way he lived with the stigma of being blind in the Wayuu society to which he belonged and also his process of appropriating the writing of Spanish, whose mastery allowed him to guarantee his subsistence and also specialize and give an invaluable contribution to the grammar and writing of the Wayuunaiki language.